$\sup × \inf$ Inequalities for the Scalar Curvature Equation in Dimensions 4 and 5 (Analysis in Theory and Applications, 2022)
We consider the following problem on bounded open set $ Ω $ of $ {\mathbb R}^n $:We assume that :Then, we have a $ \sup ×  \inf $ inequality for the solutions of the previous equation, namely: